POWER POINT: MENINGKATKAN KEMAMPUAN MEMBACA CERITA BERBAHASA INGGRIS DI SDN KARANGTENGAH 04 - Octario Eko Wahyudi; Hesty Puspita Sari (Program Studi PGSD Universitas Flores, 2023)
The objective of this research is to know the effectiveness of Power Point to improve student reading English for 5th grade of elementary school. This research was conducted with an experimental method. In conducting the study, the researcher involved the English teacher, the school principal, and the student grade 5th. This research was conducted at SDN Karangtengah 04 Blitar City. The subject of this research contain of 23 students, 14 male and 9 female. The data were obtained a pre-test, giving treatment, and post-test. After analyzing the data, it was found that the use of power point can improve students' English reading. In particular, they showed an increase in their ability to read English vocabulary. In addition, the test shows several other benefits, such as students find the meaning of stories faster, the learning atmosphere is more fun, and it increases students' interest in reading. Suggestions for teaching teachers are to use power point to teach students because it can improve students' reading skills.